Hello, let's note a this positive real number.
The sum of the square is
[tex]a^2+(a-4)^2[/tex]
right?
So, we need to solve
[tex]a^2+(a-4)^2=72[/tex]
We will develop, simplify.
Let's do it!
[tex]a^2+(a-4)^2=72\\\\a^2+a^2-8a+16=72\\\\2a^2-8a+16-72=0\\\\2(a^2-4a-28)=0\\\\a^2-4a-28=0[/tex]
Now, we can use several methods to move forward. Let's complete the square.
[tex]a^2-4a=a^2-2*2*a=(a-2)^2-2^2=(a-2)^2-4[/tex]
So,
[tex]a^2-4a-28=0\\\\(a-2)^2-4-28=0\\\\(a-2)^2=32=4^2*2\\\\a-2=\pm4\sqrt{2}\\\\a = 2(1+2\sqrt{2}) \ \ or \ \ a = 2(1-2\sqrt{2})[/tex]
As a should be positive, the solution is
[tex]\Large \boxed{\sf \bf \ \ a = 2(1+2\sqrt{2}) \ \ }[/tex]
and the other number is
[tex]2(1+2\sqrt{2})-4=2(2\sqrt{2}-1)[/tex]
Thank you.